NECESSARY BANK GUARANTEES FOR THE INTERNATIONAL PROJECTS IMPLEMENTATION IN CONSTRUCTION - Aničić, Dušan; Nestorović, Olgica (Journal of process management and new technologies, 2019)
Construction industry is an activity connected to a large number of other activities and it influences their development significantly. Construction in Serbia has a long and successful tradition in the international markets, but currently, there is little participation of our companies in the international markets and it is far from the available possibilities. Following the collapse of the largest construction companies during the transition process, new companies are developed and they need institutional and financial help and support to appear in demanding international market.This paper emphasizes the necessity to provide bank guarantees required by investors in the implementation of the international projects, with the aim of securing work quality and contractual deadlines. One of the solutions is to create a Development Bank with the appropriate support for the construction companies in acquiring business in the international market.